Analysis of Kandis Acid as a Study of Science and Socio-Cultural Benefits in Society - Hanafis Sastra Winata; Khairani Fitri; Rani Monalisa Hutagaol; Hafizhatul Abadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The main ingredient of kandis acid is the asam padeh part, which is a typical Indonesian food that has a sour and spicy taste and is then processed into instant spices. This study aims to analysis of kandis acid as a study of science and socio-cultural benefits in society. This study used descriptive analysis and the disc diffusion method using several concentrations of ethanol extract of kandis acid leaves, namely 15%, 25%, and 35%, positive control 1% chloramphenicol (w/v), and 1% (v/v) DMSO negative control. The diameter of the inhibition zone produced in the test of ethanol extract from kandis acid leaves against Staphylococcus aureus bacteria, respectively: 10.73 mm; 11.61 mm; 12.98 mm and 25.5 mm for positive control, while for Escherichia coli bacteria, namely: 6.11 mm; 8.16mm; 10.85mm; and positive control 22.75 mm. The results of statistical tests showed that there was a significant difference, meaning that the concentration had an effect on the inhibition zone formed. In conclusion, the ethanolic extract of kandis acid leaves has antibacterial activity against the growth of Staphylococcus aureus and Escherichia coli bacteria. The instant asam padeh seasoning is made from a mixture of various spices and also kandis acid which has a yellowish-orange color.